1989
DOI: 10.1007/bf00024665
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes of free-base, riboside, ribotide and glucoside cytokinins in developing rice grains

Abstract: Rice grains at various growth stages were analysed for endogenous free-base, riboside, ribotide and glucoside cytokinins on the basis of GC/MS and GC/SIM using deuterium-labeled internal standards . Cytokinins identified were trans-and cis-zeatins, transand cis-ribosylzeatins, isopentenyladenosine, isopentenyladenosine monophosphate, transand cis-ribosylzeatin monophosphates, trans-and cis-zeatin-O-glucosides, trans-and cisribosylzeatin-O-glucosides and zeatin-9-glucoside (trans/cis geometry was not determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…1B). In agreement with previous studies (Jones et al, 1990), zeatin riboside was higher than zeatin, and although several additional cytokinin compounds have been detected in maize kernels (von Staden and Forsyth, 1986), a11 cytokinin compounds appear to have the same time course of accumulation during development (Takagi et al, 1989;Jones et al, 1990). Similar patterns of transient cytokinin accumulation by whole kemels and associated tissues have been reported for several cereal-grain species (Rademacher and Graebe, 1984;Mengel et al, 1985;Lee et al, 1989;Takagi et al, 1989), including maize (Jones et al, 1990).…”
Section: Endogenous Cytokinin and Auxinsupporting
confidence: 91%
See 2 more Smart Citations
“…1B). In agreement with previous studies (Jones et al, 1990), zeatin riboside was higher than zeatin, and although several additional cytokinin compounds have been detected in maize kernels (von Staden and Forsyth, 1986), a11 cytokinin compounds appear to have the same time course of accumulation during development (Takagi et al, 1989;Jones et al, 1990). Similar patterns of transient cytokinin accumulation by whole kemels and associated tissues have been reported for several cereal-grain species (Rademacher and Graebe, 1984;Mengel et al, 1985;Lee et al, 1989;Takagi et al, 1989), including maize (Jones et al, 1990).…”
Section: Endogenous Cytokinin and Auxinsupporting
confidence: 91%
“…Studies of hormone concentrations in cereal-grain kernels (caryopses) have indicated that cytokinin is maximal at early stages (Rademacher and Graebe, 1984;Mengel et al, 1985;Lee et al, 1989;Takagi et al, 1989;Jones et al, 1990), overlapping with endosperm cell division (Chojeck et al, 1986;Ober et al, 1991), whereas IAA is maximal at later stages (Rademacher and Graebe, 1984;Mengel et al, 1985;Lee et al, 1989). However, these temporal associations have not established the functions of cytokinin and auxin in developing kernels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a bacterial system, the maize cytokinin receptor ZmHK1 responded to cZ and tZ with comparable affinities (Yonekura-Sakakibara et al, 2004;Lomin et al, 2011). cZ and its derivatives are abundant not only in maize but also in other species, including chickpea (Cicer arietinum; Emery et al, 1998) and rice (Oryza sativa; Takagi et al, 1985Takagi et al, , 1989Kojima et al, 2009). In addition, a recent comprehensive screen showed that higher levels of cZ than tZ derivatives can be found in species across the complete evolutionary tree of land plants (Gajdošová et al, 2011).…”
mentioning
confidence: 99%
“…The evidence for the regulatory functions of cytokinins has been obtained by correlation between grain weight and the level of endogenous cytokinins in barley and wheat by Michael et al (1970) and Herzog and Geisler (1982). The highest amounts of cytokinins were recorded at the early growth stages, viz., heading or anthesis or at milk stage, suggesting that the cytokinins may play important role in grain development (Takagi et al, 1989). Analysis of cytokinin levels in developing grains of wheat and rice grains has shown a large transient increases in zeatin (Z) and zeatin riboside (ZR) contents, which coincided with the period of maximum endosperm cell division (Morries et al, 1993).…”
Section: Hormonal Regulation Of Grain Developmentmentioning
confidence: 99%